Public Goods and the Technology of Consumption: A Correction - Sandmo, Agnar (Review of Economic Studies, 1975)
Parts II-IV of [1] are concerned with the simple case where there is a one-to-one-to-one relationship between private goods, public goods and final goods. Section V attempts to generalize the analysis in this respect by allowing for the fact that it will typically be the case that a private or a public good enters into several production functions for final goods. Let there be n final goods, q private goods and t public goods, and consider the following two alternative versions of consumers' production functions for final goods: